NUTRITIONAL SUPPLEMENTS FROM GRAIN WITH MACRO- AND MICROELEMENT COMPOSITION OF SPROUTED COBS - I.R. Askarov; D.T. Khasanova (European Journal of Agricultural and Rural Education, 2024)
This article delves into the myriad benefits of nutritional supplements derived from grain with a focus on the macro- and microelement composition of sprouted cobs. A comprehensive exploration of the advantages associated with grains featuring sprouted cobs is presented, emphasizing their pivotal role in crafting nutritional supplements tailored for Functional Nutrition. Additionally, the article provides a practical and convenient method for home harvesting and preparation of wheat grain. Through rigorous studies, the macro- and microelement content of a novel nutritional supplement, derived from wheat grain, is meticulously analyzed. The findings illuminate the nutritional richness of the supplement, offering valuable insights for those seeking to enhance their dietary well-being